A Short History of Nearly Everything: A Journey Through Space and Time - Bryson, Bill (London: Penguin Random House, 2003)
Bill Bryson describes himself as a reluctant traveller, but even when he stays safely at home he can't contain his curiosity about the world around him. "A Short History of Nearly Everything" is his quest to understand everything that has happened from the Big Bang to the rise of civilisation - how we got from there, being nothing at all, to here, being us. The ultimate eye-opening journey through time and space, revealing the world in a way most of us have never seen it before.
Includes notes, bibliography and index
Keywords: Science$1 (BHistorys -- Astronomy -- Earth sciences -- Life sciences